2022
DOI: 10.1002/adfm.202203402
|View full text |Cite
|
Sign up to set email alerts
|

Yield‐Stress and Creep Control Depot Formation and Persistence of Injectable Hydrogels Following Subcutaneous Administration

Abstract: Hydrogels that can be injected into the body using standard needles or catheters enable a minimally invasive strategy to prolong local delivery of therapeutic cargo. In particular, physically cross‐linked hydrogels exhibit shear‐thinning and self‐healing behaviors enabling facile injectability and depot formation upon administration. While prior efforts to characterize these systems have focused on injectability and cargo release behaviors, prediction of cargo release in the body often assumes these materials … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…We observed a dramatically decreasing viscosity with an increasing shear rate, thereby confirming the hydrogels’ ability to shear-thin, which is necessary for facile injectability. A stress-controlled flow sweep was also performed to measure the hydrogels’ yield stresses, a critical characteristic for maintaining a robust depot upon administration, [13,19] by determining the stress where the viscosity decreases by 3 orders of magnitude (Figure 2c). We observed decreasing yield stresses as network density decreased, suggesting shorter depot lifetimes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a dramatically decreasing viscosity with an increasing shear rate, thereby confirming the hydrogels’ ability to shear-thin, which is necessary for facile injectability. A stress-controlled flow sweep was also performed to measure the hydrogels’ yield stresses, a critical characteristic for maintaining a robust depot upon administration, [13,19] by determining the stress where the viscosity decreases by 3 orders of magnitude (Figure 2c). We observed decreasing yield stresses as network density decreased, suggesting shorter depot lifetimes.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo erosion of the hydrogels, which can also be measured as the persistence time of the hydrogels in the subcutaneous space, has been previously reported. [19] Half-lives of hydrogel retention were found to be 8.5 days for PNP-1-5 and 10.9 days for PNP-1-10. While the half-life of hydrogel retention was not measured for PNP-2-10, prior work has also demonstrated that yield stress and pre-shear viscosity are respectively predictive of depot formation and depot persistence time.…”
Section: Resultsmentioning
confidence: 99%
“…50 Both of these formulations exhibit sufficiently high yield stress to form a persistent depot in the mouse subcutaneous space upon injection. 48 In addition, the hydrogel is rheologically stable for more than 5 weeks at room temperature (Fig. S2 †).…”
Section: Paper Biomaterials Sciencementioning
confidence: 97%
“…50 Finally, the yield stress of each formulation was determined to assess the ability of the depot to retain its shape under the forces present at the site of injection; it has previously been demonstrated that yield stress is an important rheological property for subcutaneous depot formation and retention. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Yield stresses of 70 and 350 Pa were measured for the 1:5 and 2:10 formulations, respectively (Fig. 2g).…”
Section: Paper Biomaterials Sciencementioning
confidence: 99%
See 1 more Smart Citation